The ecomorphic projection of soil mesofauna spatial organization - Кунах, О. М.; Жуков, О. В.; Балюк, Ю. О. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2013)
In the work, the results of study of the spatial organization of soil urbazem mesofauna have been processed by OMI-analysis methods. The vegetation has typically meadow megatrophic and mesophylic character that favorable for high level of soil mesofauna abundance (212 ind./m2). In ecological structure of soil animal community such groups as saprophages, paludants, ultra-hygrophils, mesotrophocoenomorphes, epigeic topomorphes are dominant. The measured edafic characteristics such as soil penetration resistance, electrical conductivity, litter depth and vegetation height have been shown to play an important role in structuration of an ecological niche of mesopedobionts community. First two axes of the OMI-analysis have been found to describe 77,82% of inertia that is quite enough for the description of differentiation of mesofauna ecological niches on investigated range in space of the first two axes. Marginality average value (OMI=4,68) is significant for р=0,01 that testifies to an important role of the selected variables of environment for structuration of community of soil mesofauna. In the result of RLQ-analysis and following cluster procedures there have been revealed three key functional groups of mesopedobionts and the role of edafic factors in their spatial variation have been established.